Effects of TRPV1 Activation by Capsaicin and Endogenous N-Arachidonoyl Taurine on Synaptic Transmission in the Prefrontal Cortex - Zhang, Mingyue; Ruwe, David; Saffari, Roja; Kravchenko, Mykola; Zhang, Weiqi (Frontiers in Neuroscience, 2020)
Abstract While the transient receptor potential vanilloid 1 (TRPV1) ion channel, a non-selective calcium-permeable cation channel with high Ca2+ permeability, mainly integrates physical and chemical stimuli for nociception, recent studies suggest that it has a role beyond a noxious thermal sensor. In fact, TRPV1 is presently being considered as a target for treating pathophysiological processes including pain, fear and anxiety disorders. Although this ion channel has many potential roles, its underlying mechanism of action remains elusive. Here we show in mice that activation of TRPV1-, by the exogenous agonist capsaicin-, regulates synaptic activity in both glutamatergic and GABAergic synaptic transmission. Moreover, activation by the endogenous activator N-arachidonoyl taurine (NAT), induced similar effects as capsaicin. On the other hand, taurine, the decomposition product of NAT, strongly depressed the evoked glutamatergic synaptic transmission. In addition to these findings, we also show the immunohistochemical distribution of TRPV1 in the prefrontal cortex of mice, as such studies are currently less frequent in the PFC. Overall, these observations allow for a better understanding of how TRPV1 helps regulate excitatory and inhibitory synaptic activity in the PFC of mice. Keywords: GABAergic inhibition; glutamatergic; NAT; PFC; TRPV1; taurine